2015
DOI: 10.1021/acs.est.5b01129
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Facilitates the Conjugative Transfer of Antibiotic Resistance Genes Mediated by Plasmid RP4

Abstract: The dissemination and propagation of antibiotic resistance genes (ARGs) is an emerging global health concern. In our previous study, the ionic liquid (IL) 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIm][PF6]) had been proven to facilitate the dissemination of ARGs via horizontal gene transfer. In this study, we further confirm that this compound facilitates the horizontal transfer of plasmid RP4 through a conjugation mechanism and not by natural transformation. The mechanisms for [BMIm][PF6] promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(68 citation statements)
references
References 54 publications
3
65
0
Order By: Relevance
“…ARGs are able to horizontally spread between bacteria via transformation or conjugation under antibiotic stresses, thereby ARGs being enriched in the human-impacted environment (Cottell et al, 2014;Turner et al, 2014). Such gene transfers require plasmids as the shuttling carriers between bacteria (Wang et al, 2015). For instance, the concurrence of metal and antibiotic resistance genes in the plasmids facilitates the dissemination of these genes under elevated stresses caused by either heavy metals or antibiotics (Li et al, 2015a;Zhai et al, 2016).…”
Section: Mechanisms Proposed For Accumulation Of Args In the Pahs-conmentioning
confidence: 99%
See 1 more Smart Citation
“…ARGs are able to horizontally spread between bacteria via transformation or conjugation under antibiotic stresses, thereby ARGs being enriched in the human-impacted environment (Cottell et al, 2014;Turner et al, 2014). Such gene transfers require plasmids as the shuttling carriers between bacteria (Wang et al, 2015). For instance, the concurrence of metal and antibiotic resistance genes in the plasmids facilitates the dissemination of these genes under elevated stresses caused by either heavy metals or antibiotics (Li et al, 2015a;Zhai et al, 2016).…”
Section: Mechanisms Proposed For Accumulation Of Args In the Pahs-conmentioning
confidence: 99%
“…Moreover, ARGs could be amplified in the environment under elevated selective stress via two distinct pathways, viz. the overgrowth of ARGs-carrying indigenous bacteria, or horizontal gene transfer of ARGs between bacteria using mobile gene elements (MGEs) as the carriers (e.g., plasmids, transposons and integrons) (Engelstadter et al, 2016;Knapp et al, 2008;Wang et al, 2015). Therefore, analysis of bacterial community and identification of genetic location of ARGs could be beneficial to gain more insights about how ARGs are accumulated in the PAHs-contaminated soils.…”
Section: Introductionmentioning
confidence: 99%
“…Urban wastewater treatment plants (UWWTPs) are at the interface between human population and the aquatic/soil environments, may provide an ideal setting for the acquisition and dissemination of antibiotic resistance, because a diverse mixture of antibiotics and other pollutants, their metabolites and resistant bacteria, reaches UWWTPs through wastewater discharges from hospitals, households, industries and animal farms (Guo et al, 2017). The prevalence of ARB and ARGs in UWWTPs has attracted more and more attention recently (Chen and Zhang 2013, Naquin et al, 2015, Wang et al, 2015, Wen et al, 2016. In particular, biological reactors in activated sludge systems are thought as one of critical compartments in harboring both ARB and ARGs (Rizzo et al, 2013, Yang et al, 2012, through selection under exposure of antibiotic or resistance transfer among bacteria via horizontal gene transfer (HGT) (Jutkina et al, 2016, Kim et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, biological reactors in activated sludge systems are thought as one of critical compartments in harboring both ARB and ARGs (Rizzo et al, 2013, Yang et al, 2012, through selection under exposure of antibiotic or resistance transfer among bacteria via horizontal gene transfer (HGT) (Jutkina et al, 2016, Kim et al, 2014. More importantly, it has been reported that UWWTPs exhibit limited capacity to remove or control ARGs and ARB (Munir et al, 2011, Pruden et al, 2006, Wang et al, 2015. Worryingly, not only does the effluent M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 represent an important reservoir containing various ARGs, but also the abundances of some typical ARGs are even higher in effluent than that in influent via the treatment processes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigation of the transfer of eARGs can aid in better understanding and clarification of their contribution to the dissemination of ARGs. In previous studies, naked DNA (extracted from donor bacteria) was directly added to the recipient system and used as control for ruling out the natural transformation in the conjugative transfer process [28]. However, this method does not accurately estimate the interference of transformation.…”
Section: Introductionmentioning
confidence: 99%